Load inventory survey of Curtin University Malaysia - Palanichamy, Chinnasamy (2015)
As an important part of economical society, higher educational institutions and universities have been shouldering the responsibilities towards quality education, scientific research and social services throughout the world. However, they are found to be one of the major consumers of energy and the universities in Malaysia also have been identified as foremost energy consumers in the country. In order to follow energy conservation measures, a comprehensive energy audit becomes essential to determine how and where the energy is being consumed in a facility. In this study, the load inventory technique is adapted comprehensively to determine the different load categories in the university campus in terms of their connected demand, actual demand and total consumption. Based on the load inventory, an analysis has been carried out to identify the diversity and load factors and suggestions are given to improve them.